Antiquitin Deficiency with Adolescent Onset Epilepsy: Molecular Diagnosis in a Mother of Affected Offsprings - Srinivasaraghavan, Rangan; Parameswaran, Narayanan; Mathis, Deborah; Bürer, Celine; Plecko, Barbara (Neuropediatrics, 2018)
Antiquitin deficiency is the most prevalent form of pyridoxine-dependent epilepsy. While most patients present with neonatal onset of therapy-resistant seizures, a few cases with late-onset during infancy have been described. Here, we describe the juvenile onset of epilepsy at the age of 17 years due to antiquitin deficiency in an Indian female with homozygosity for the most prevalent ALDH7A1 missense mutation, c.1279G > C; p.Glu427Gln in exon 14. The diagnosis was established along familial cosegregation analysis for an affected offspring, that had neonatal pyridoxine responsive seizures and had been found to be compound heterozygous for c.1279G > C; p.Glu427Gln in exon 14 and a nonsense mutation c.796C > T; p.Arg266* in exon 9. While seizures in the mother had been incompletely controlled by levetiracetam, she remained seizure-free on pyridoxine monotherapy, 200 mg/day. Her fourth pregnancy resulted in a female affected offspring, who was treated prospectively and never developed seizures with a normal outcome at age 2 years while on pyridoxine. This report illustrates that the phenotypic spectrum of antiquitin deficiency is still underestimated and that this treatable inborn error of metabolism has to be considered in case of therapy-resistant seizures even at older age. It furthermore supports prospective in utero treatment with pyridoxine in forthcoming pregnancies at risk.
Keywords: late-onset; genotype -phenotype; intrauterine treatment; prenatal; PDE; therapy resistance